Analisis Pengaruh Faktor Kebudayaan, Sosial, Dan Pribadi Terhadap Perilaku Nasabah dalam Menabung di Bank Jateng Cabang Koordinator Semarang - Teguh Setiawan; Ulil Amri (Jurnal Ilmiah Aset, 2017)
This study was to analyze the influence of cultural, social and personal factor on customer saving behavior at Semarang Coordinator Branch of Bank Jateng. In this study the population was the customer who saved in Bank Jateng Semarang Coordinator Branch in 2015 amounted to 42.176 customers. While in this study the samples were 100 people. The data analysis technique used in this study was multiple linear regression analysis. The results showed partially cultural factor influenced positively and significantly on customer behavior in saving, social factor influenced positively and significantly on customer behavior in saving, personal factor influenced positively and significantly on customer behavior in saving. While simultaneously cultural factor, social factor and personal factor influenced customer behavior in saving at Bank Jateng.